Pesticide responses of Arctic and temperate microalgae differ in relation to ecophysiological characteristics - Du, Juan; Izquierdo, Disney; Naoum, Jonathan; Ohlund, Leanne; Sleno, Lekha; Beisner, Beatrix E.; Lavaud, Johann; Juneau, Philippe (Aquatic Toxicology, 2023)
Polar ecosystems play an important role in global primary production. Microalgae have adaptations that enable them to live under low temperature environments where irradiance and day length change drastically. Their adaptations, leading to different ecophysiological characteristics relative to temperate species, could also alter their sensitivity to pollutants such as pesticides. This study's objective was to understand how different ecophysiological characteristics influence the response of Arctic phytoplankton to pesticides in relation to the responses of their temperate counterparts. Ecophysiological endpoints were related to growth, cell biovolume, pigment content, photosynthetic activity, photoprotective mechanisms (NPQ, antioxidant enzyme activities), and reactive oxygen species (ROS) content. The Arctic species Micromonas polaris was more resistant to atrazine and simazine than its temperate counterpart Micromonas bravo. However, the other Arctic species Chaetoceros neogracilis was more sensitive to these herbicides than its temperate counterpart Chaetoceros neogracile. With respect to two other pesticide toxicity, both temperate microalgae were more sensitive to trifluralin, while Arctic microalgae were more sensitive to chlorpyrifos (insecticide). All differences could be ascribed to differences in the eco-physiological features of the two microalgal groups, which can be explained by cell size, pigment content, ROS content and protective mechanisms (NPQ and antioxidant enzymes).